TECHNOLOGY FOR DEVELOPING STUDENTS’ REFLECTIVE THINKING THROUGH MODERN PEDAGOGICAL TECHNOLOGIES (Scientific journal of the Fergana State University, 2026)
This article explores the use of modern pedagogical technologies as a key factor in developing students’ reflective thinking. Reflective thinking is defined as a metacognitive process that enables learners to analyze, evaluate, and improve their own learning experiences. The paper discusses how interactive teaching methods, project-based learning, information and communication technologies (ICT), and the flipped classroom model contribute to the formation of reflective awareness and autonomous learning. It also examines the pedagogical conditions necessary for enhancing reflection, highlighting the teacher’s role as a facilitator and the importance of learner-centered education.